Peripheral microcirculation adaptations in response to the addition of Inspiratory Muscle Training in heart failure cardiac rehabilitation regimen - Kourtidou, Soultana; Katsoula, Christina; Vagionas, Dimitrios; Briasoulis, Alexandros; Vasileiou, Ioannis; Rovina, Nikoleta; Papadopoulou, Elektra; Routsi, Christina; Nanas, Serafeim; Vasileiadis, Ioannis; Karatzanos, Eleftherios (Health & Research Journal, 2025)
Background: Exercise intolerance, dyspnea on exertion and respiratory muscle fatigue are predominant features of chronic heart failure adding to disease severity. Inspiratory Muscle Training (IMT) has been recently integrated into traditional exercise-based cardiac rehabilitation regimens. We opted to evaluate the effect of IMT on the peripheral muscle microcirculation of patients with stable chronic heart failure participating in cardiac rehabilitation. Method and Material: Twenty-five stable patients with chronic heart failure underwent cardiac rehabilitation with aerobic exercise and resistance training 3×/week for 12 weeks. Subjects were randomly assigned to the intervention group that performed IMT or the control group that performed Sham-IMT in addition to standard CR regimen. Systemic microcirculation was assessed via near-infrared spectroscopy (NIRS) and the 3-min vascular occlusion technique at the thenar muscle. Cardiorespiratory exercise testing, pulmonary function and muscle strength assessment were also performed, at baseline and following completion of the cardiac rehabilitation program. Results: Both groups equally improved their cardiorespiratory fitness, left ventricular ejection fraction and muscle strength (p>0.05 for between-group comparisons). The intervention group showed higher NIRS-derived reperfusion rate, maximum inspiratory pressure and lung function as compared to the control group (p<0.05). Conclusions: Reperfusion rate is a known surrogate for endothelial function. Therefore, the addition of structured IMT in targeted cardiac rehabilitation marked beneficial effects on systemic microcirculation.